2020
DOI: 10.1038/s41598-020-66038-1
|View full text |Cite
|
Sign up to set email alerts
|

31-year contrasting agricultural managements affect the distribution of organic carbon in aggregate-sized fractions of a Mollisol

Abstract: Evaluation of soil organic carbon (SOC) dynamics is often limited by the complexity of soil matrix. Quantitative information on the distribution of SOC within aggregate hierarchy will help elucidate the carbon flow in soil matrix. However, this knowledge still needs to be documented. Soils were sampled from a surface Mollisol with plots under 100 years of continuous cropping, 31 years of simulated overgrazing to severely degraded bareland, and grassland restoration from cropped soil. A combined density and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…Moreover, soil tillage might also influence SOC changes. The cessation of tillage disturbance could affect soil aggregate‐protected carbon, nutrients availability, and microclimate, thus preventing SOM decomposition (M. Sheng et al., 2020; Six et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, soil tillage might also influence SOC changes. The cessation of tillage disturbance could affect soil aggregate‐protected carbon, nutrients availability, and microclimate, thus preventing SOM decomposition (M. Sheng et al., 2020; Six et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found that SOC in subsoil was more susceptible to land use and climate changes than the topsoil (Luo et al., 2020). Moreover, there is growing evidence that SOC dynamics in the subsoil were also affected by land use changes (Poeplau & Don, 2013; M. Sheng et al., 2020), while comprehensively studies regarding the response of SOC and its fractions in subsoil to land use changes remain scarce.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations